TIKTOK EXPOSURE AND INDONESIAN HIGH SCHOOL GEN Z’S INFORMAL ENGLISH ACQUISITION: LINKS TO INFORMAL VOCABULARY AND SLANG/PRAGMATIC COMPREHENSION - Della Isa Fadillah; Mochlis Ekowijayanto (IJEE (Indonesian Journal of English Education), 2026)
TikTok has become a prominent source of informal English exposure among Indonesian Gen Z learners, particularly through short, multimodal, and interactive videos. This study investigated the relationship between English language TikTok exposure and informal English language acquisition among Indonesian high school learners. Informal English language acquisition was measured through informal vocabulary knowledge and slang/pragmatic comprehension. Employing a cross-sectional quantitative correlational design, the study involved 240 students from Grades 10–12. Data were collected using the English TikTok Exposure Scale (ETES), an Informal Vocabulary Test (IVT), and a Slang/Pragmatic Comprehension Test (SPCT). Pearson correlations, partial correlations, and hierarchical multiple regression were used to analyse the data while controlling for general English proficiency. The findings showed that overall TikTok exposure was positively correlated with informal vocabulary knowledge and slang/pragmatic comprehension. Regression results indicated that TikTok exposure indicators explained additional variance beyond general English proficiency.Caption use significantly predicted informal vocabulary knowledge, while caption use and comment reading predicted slang/pragmatic comprehension. These findings suggest that meaningful engagement with English TikTok content, rather than exposure duration alone, contributes to informal English language acquisition among Indonesian Gen Z high school learners.